2018
DOI: 10.1002/slct.201801781
|View full text |Cite
|
Sign up to set email alerts
|

SERS of Trititanate Nanotubes: Selective Enhancement of Catechol Compounds

Abstract: The surface enhanced Raman scattering of trititanate nanotubes (TiNT) modified with enediol ligands was investigated and it was found that the functional group dramatically affects the enhancement observed. For TiNT‐4‐nitrocatechol, a SERS enhancement is seen; however, when dopamine is attached, no signal is seen. The relative band gap positions upon 785 nm laser excitation are proposed to explain the observed phenomenon. This attachment is investigated by solid state NMR and UV/Vis spectroscopy and supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…We have recently investigated semiconductor SERS for TiNT modified with catechol based organic modifiers and found that the HOMO level of the system was located on the organic modifier of the charge transfer complex. [19] In addition, the catechol compounds studied resulted in band gaps for the composite being close to the laser wavelength typically used for Raman spectroscopy. Inspired by these results, the existence of the dopamine monomers and amine tail group allows us to exploit the self-assembly on the TiNT surface by dopamine to form a triad with Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…We have recently investigated semiconductor SERS for TiNT modified with catechol based organic modifiers and found that the HOMO level of the system was located on the organic modifier of the charge transfer complex. [19] In addition, the catechol compounds studied resulted in band gaps for the composite being close to the laser wavelength typically used for Raman spectroscopy. Inspired by these results, the existence of the dopamine monomers and amine tail group allows us to exploit the self-assembly on the TiNT surface by dopamine to form a triad with Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 87%
“…In our previous work, due to the bandgap of the composite being larger than the laser energy, it has been demonstrated that the TiNT-dopamine system is not activated for SERS by the lower energy 735 nm (1.687 eV) laser. [19] In this work, we use TiNT-dopamine-Ag excited with a higher energy, 532 nm (2.33 eV) laser to investigate the SERS enhancement. The results provide interesting insights into the cooperative effects of metal oxide organics and noble metal Raman enhancement.…”
Section: Surface Enhanced Raman Spectroscopymentioning
confidence: 99%
“…For instance, Liu et al found that catechol coatings selectively generate a signal in the surface-enhanced Raman scattering of trititanate nanotubes (TiNT). 12 Also, the construction of a heterojunction with secondary species has been proven to be significant to boost the solar-to-fuel conversion efficiency. In fact, mixing two components at the nanoscale provides strong interfacial interaction, improving thus the charge carrier dynamics.…”
Section: Introductionmentioning
confidence: 99%